Behind the Mirror : A Report on the Self-Evaluation Systems of the World Bank Group - Independent Evaluation Group (World Bank, Washington, DC, 2016)
The World Bank Group's self-evaluation systems have expanded since they started 40 years ago, and compliance with requirements is mostly strong. They systems mesh well with the independent evaluation systems for which they provide information and the systems have been emulated and adapted by other development agencies. However, the self-evaluation systems primarily focus on results reporting and accountability needs and do not provide the information necessary to help the Bank Group transform into a "Solutions Bank" or develop learning to enhance performance as emphasized in its 2013 strategy. Information generated through the systems is not regularly mined for knowledge and learning except by IEG, and its use for project and portfolio performance management can be improved. The systems produce corporate results measures but need to produce value to staff and line management and to the primary beneficiaries of the "Solutions Bank"—client governments, implementing agencies, firms, and beneficiaries and citizens.